Effect of Kinetic Return Ankle Foot Orthosis in Patient with Incomplete Spinal Cord Injury: Changes of the Gait Pattern. A Case Report - Margot Bergmann; Mari Alvela; Priit Eelmäe; Doris Vahtrik; Helena Gapeyeva (Lithuanian Sports University, 2018)
Background. The variety of orthotics available induces a purpose for estimation of their influence of functional mobility for individual needs in people with incomplete spinal cord injuries (ISCI). The aim of the study was to investigate the effect of the use of kinetic return ankle foot orthosis (KRAFO) on gait pattern in case of ISCI. Methods. Ankle and knee joint kinematic and kinetic characteristics during gait with and without KRAFO were studied in a 34-year-old man with ISCI (fracture v.C5) using 3D motion analysis system (Vicon Motion Systems Ltd., UK) including two dynamographic platforms (AMTI, USA). Ankle and knee joint angles at initial contact and mid-stance, ankle dorsiflexion and foot progression angle in swing phase and ankle joint push-off values in stance phase were analysed. Results.  An  excessive  dorsiflexion  in  right  ankle  joint  at  initial  contact,  in  mid-stance  and  in  swing-phase occurred when walking without the orthosis, which decreased (105, 57 and 73%, respectively, p < .01) with the use of KRAFO. Orthoses use evoked the decrease (77%, p < .01) in peak foot progression angle. Ankle joint peak push- off power was low without the use of KRAFO and decreased even more (28%, p < .05) with the use of orthosis. Decreases of knee joint flexion angle at initial contact and in mid-stance (29 and 23%, respectively) with the use of KRAFO were not significant as compared to gait without orthosis. Conclusions. Walking with KRAFO improved ankle and knee joint stability, providing a decrease in ankle kinematic characteristics but ankle joint push-off power did not change. Further studies are needed to compare the effect of KRAFO in comparison with other orthoses on gait pattern in case of ISCI in accordance with the patient- centric approach for rehabilitation process management. Keywords:  spinal cord injury, clinical gait analysis, ankle foot orthosis, kinematic and kinetic characteristics of gait.